2008
DOI: 10.1103/physreve.77.021903
|View full text |Cite
|
Sign up to set email alerts
|

Lateral migration of a two-dimensional vesicle in unbounded Poiseuille flow

Abstract: The migration of a suspended vesicle in an unbounded Poiseuille flow is investigated numerically in the low Reynolds number limit. We consider the situation without viscosity contrast between the interior of the vesicle and the exterior. Using the boundary integral method we solve the corresponding hydrodynamic flow equations and track explicitly the vesicle dynamics in two dimensions. We find that the interplay between the nonlinear character of the Poiseuille flow and the vesicle deformation causes a cross-s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
155
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(167 citation statements)
references
References 26 publications
(43 reference statements)
9
155
0
1
Order By: Relevance
“…We showed that the effects of the walls and of the curvature of the velocity field are coupled in a nonlinear manner: Curvature not only induces migration 27 but also affects the shape and orientation, which affects the lift force. The law v m ϳ ␥ ͑y͒ / y markedly differs from what the naive extrapolation of the results for a vesicle near a wall and in a linear shear flow would give v m ϳ ␥ ͑y͒ / y 2 .…”
Section: ͑4͒mentioning
confidence: 98%
See 1 more Smart Citation
“…We showed that the effects of the walls and of the curvature of the velocity field are coupled in a nonlinear manner: Curvature not only induces migration 27 but also affects the shape and orientation, which affects the lift force. The law v m ϳ ␥ ͑y͒ / y markedly differs from what the naive extrapolation of the results for a vesicle near a wall and in a linear shear flow would give v m ϳ ␥ ͑y͒ / y 2 .…”
Section: ͑4͒mentioning
confidence: 98%
“…[22][23][24][25] In agreement with the numerical and theoretical studies for simple shear flows, 22,24 we showed recently that the migration velocity decreases like 1 / y 2 , where y is the distance to the wall of the center of mass of the vesicle. 26 ͑ii͒ The nonconstant shear rate in a parabolic velocity profile ͑even unbounded͒ leads to a subtle interplay between the gradient of shear and the shape, 27 resulting in migration toward the center with a constant drift velocity except near the centerline. In a realistic channel, both effects coexist and we shall see that this leads to a new and nontrivial noninertial migration law.…”
mentioning
confidence: 99%
“…This has been achieved by using ad hoc membrane forces that penalize any deviation from the equilibrium configuration. In the present paper we use the precise analytical expression of the local membrane force as it has been derived [15] from the known Helfrich bending energy [16]. The perimeter conservation in our case is achieved by using a field of local Lagrangian multiplicators (equivalent to an effective tension).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike RBCs, for vesicles we can vary their intrinsic characteristic parameters (e.g., size, degree of deflation, and nature of internal fluid). Despite the simplicity of their structure, vesicles have exhibited many features observed for red blood cells: equilibrium shapes [21], tank-treading motion [3,22], lateral migration [15,23,24], or slipperlike shapes [25,26]. Capsules (a model system incorporating shear elasticity) have also revealed some common features with vesicles [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The kinematic viscosity n and the surface tension s are given by 10) with x being the coordinate normal to the interface.…”
Section: 4) Andmentioning
confidence: 99%